Golden5: a proposed construction of a good learning environment - Rita de Cássia de Souza; Maria Jose Lera Rodriguez (Universidade Federal de Santa Maria, 2014)
The educational intervention Golden5 Program was created in 2004 by an international team to improve the school environment in se - condary education by passing similar difficulties in several coun - tries. Currently, its use has been extended to preschools, primary and extracurricular activities for students with learning difficulties. The Golden5 aims to improve the school environment and its effec - tiveness from the teacher intervention. Therefore, offers teachers a set of tools and skills that help to understand the functioning of the group and manage it more adequately. Several studies on the imple - mentation of Golden5 in several countries, including internal and external evaluations of the Program, showed very positive results. Nevertheless, one must consider that the application of Golden5 depends on motivation and efficiency of teachers and that certainly affects the results.